Can you see it too? Observed and self-rated participation in mainstream schools in students with and without autism spectrum disorders - Falkmer, Marita; Oehlers, Kirsty; Granlund, M.; Falkmer, Torbjorn (Informa Healthcare, 2015)
Objectives: To examine the degree to which observations can capture perception of participation, observed and self-rated levels of interactions for students with and without autism spectrum disorders (ASD) were explored.Methods: Frequencies and levels of involvement in interactions with classmates were observed and compared in 22 students with ASD and 84 of their classmates in mainstream schools, using a standardized protocol. Self-reported participation measurements regarding interactions with classmates and teachers from five questionnaire items were correlated with the observations. In total, 51 516 data points were coded and entered into the analyses, and correlated with 530 questionnaire ratings.Results: Only one weak correlation was found in each group. Compared with classmates, students with ASD participated less frequently, but were not less involved when they actually did.Conclusions: Observations alone do not capture the individuals’ perception of participation and are not sufficient if the subjective aspect of participation is to be measured.